Food Waste-Derived Biomaterials Enriched by Biostimulant Agents for Sustainable Horticultural Practices: A Possible Circular Solution - Mapelli, Francesca; Carullo, Daniele; Farris, Stefano; Ferrante, Antonio; Bacenetti, Jacopo; Ventura, Vera; Frisio, Dario; Borin, Sara (Frontiers in Sustainability, 2022)
The horticultural industry claims the substitution of plastic plantlet containers, which derive from oil-based raw materials and cannot be recycled, with bio-based ones, aiming to decrease waste management costs and increase the overall production sustainability. Bio-based fully biodegradable nursery pots can be directly placed in soil, thus decreasing the plantlet transplant stress and labor, and avoiding waste generation. The development of biomaterials specifically obtained from food-derived wastes like fruit and vegetables will add further advantages by an improved use of resources, the production of added-value materials and the replenishment of food losses, in a perfect circular economy approach. A multidisciplinary strategy combining material science, microbiology, agronomy and economy will, moreover, allow the development of functionalized food-waste derived materials, enriched in biostimulant extracts, alive plant-growth promoting microorganisms and thermal buffering molecules, obtaining biodegradable and biofertilising plant multiplication plugs with the potential to increase the sustainability of the overall agri-food production chain.